Scramble Learning Model with the Assistance of Word Box Media: Beginning Reading Ability of Elementary School Students - Andriyani, Viki; Fatoni, A; Hasnanto, Anton Tri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Early reading skills are a crucial foundation in elementary school but are often a challenge for first-grade students. Therefore, this study aims to examine the effect of implementing the Scramble learning model mediated by word boxes on improving early reading skills in elementary school students. This study uses a quantitative approach with a pre-experimental research type of one-group pretest-posttest design. The study population was all first-grade students at elementary school 3 Way Galih, South Lampung. The research sample consisted of 38 first-grade students. The instrument used was a written test of early reading skills given in the form of a pretest (before treatment) and a posttest (after treatment). Data analysis was carried out using a paired sample t-test. The results of descriptive statistics showed a significant increase in students' abilities, evidenced by an increase in the average score from 46.18 (pretest) to 69.87 (post test). The results of the paired sample t-test hypothesis test showed a Sig. (2-tailed) value of 0.000. Because the Sig. (0.000) is smaller than alpha = 0.05, then H0 is rejected and Ha is accepted. These results demonstrate that the Scramble learning model with word box media improves word stringing and beginning reading. This study shows that the simple and interactive Scramble learning model, supported by word box media, can help teachers overcome beginning reading difficulties and motivate elementary school students.